Advances in Agricultural Biotechnology - K.C., Mamata; Lamichhane, Anuj (Nepal Journal of Biotechnology, 2021)
Agricultural biotechnology is becoming the major sector in crop improvement through the use of scientific techniques for the modification of genes conferring resistance to biotic, abiotic stress and improving the quality of crops. With the evolvement from Mendelian genetics to molecular biotechnology, there have been several developments in the field of crop improvement. Recent biotechnological advances have aimed towards removing the physiological constraints of the crops and increasing crop yield potential. With the use of different tools of agricultural biotechnologies like genetic engineering, tissue culture, embryo rescue, somatic hybridization, molecular marker-assisted selection, genome doubling, and omics technologies, various transgenic crops have been developed over the decades and have been approved for commercialization. This development and adoption of transgenic technology have been shown to increase crop yields, reduce CO2 emission, reduce pesticide and insecticide use and decrease the costs of crop production. Even though the biotechnological approach and transgenic organisms have immense potential to contribute to the world’s food security, several concerns of genetically modified crops being a threat to the environment and human health have developed. This review will address applications and concerns of biotechnology in crop improvement considering health hazards and ecological risks.